2020
DOI: 10.2147/ijn.s249205
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dual Receptor-Targeted and Redox-Sensitive Polymeric Micelles Self-Assembled from a Folic Acid-Hyaluronic Acid-SS-Vitamin E Succinate Polymer for Precise Cancer Therapy</p>

Abstract: Poor site-specific delivery and insufficient intracellular drug release in tumors are inherent disadvantages to successful chemotherapy. In this study, an extraordinary polymeric micelle nanoplatform was designed for the efficient delivery of paclitaxel (PTX) by combining dual receptor-mediated active targeting and stimuli response to intracellular reduction potential. Methods: The dual-targeted redox-sensitive polymer, folic acid-hyaluronic acid-SS-vitamin E succinate (FHSV), was synthesized via an amidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Continuous angiogenesis, one of the features of tumor development, plays a driving role in the process of TME shift in the direction of immune escape occurrence (118). Rapid tumor proliferation is always accompanied by angiogenesis to meet the needs of tumor cells for oxygen and nutrition (126). Additionally, tumor cells' aberrant angiogenesis is unable to carry enough oxygen.…”
Section: Tmes Develop Icis Resistance As a Results Of Immune Evasionmentioning
confidence: 99%
“…Continuous angiogenesis, one of the features of tumor development, plays a driving role in the process of TME shift in the direction of immune escape occurrence (118). Rapid tumor proliferation is always accompanied by angiogenesis to meet the needs of tumor cells for oxygen and nutrition (126). Additionally, tumor cells' aberrant angiogenesis is unable to carry enough oxygen.…”
Section: Tmes Develop Icis Resistance As a Results Of Immune Evasionmentioning
confidence: 99%
“…A mixed solution of red blood cell suspension (1.25 mL) and ultrapure water (1.25 mL) was set as the positive control. After incubation for 3 h at 37 °C and centrifugation (1500 rpm, 15 min), the absorbance of the supernatant at 540 nm was measured by an ultraviolet–visible spectrophotometer (Yang et al., 2020 ). Percent hemolysis was calculated according to the following equation.…”
Section: Methodsmentioning
confidence: 99%
“…The resveratrol derivative is 3,5,4′-trimethoxy-trans-stilbene (BTM) and it is loaded in the PEG–PE micelles acting against colon cancer cells (CT26 cells) reporting anti-cancer efficacy and in tumor-bearing mice with an improved half-life and increased bioavailability [ 17 ]. Paclitaxel was effectively delivered to the tumor site with the help of the folic acid-hyaluronic acid-SS-vitamin E succinate polymer which enhanced selective targeted toxicity to the cancer cells without damaging healthy cells by analyzing cytotoxicity, apoptosis and cellular uptake studies in MCF-7 and NIH3T3 cells [ 18 ]. Studying the retention effects and skin penetration of thiolatedpluronic f127 polymeric micelles loaded with berberine using in vitro transdermic and fluorescence microscopy analysis showed that preparations enhanced the therapeutic benefit by decreasing the entry of drugsinto the systemic circulation, thereby preventing side effects and effectively treatinglocal skin diseases [ 19 ].…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%